Hydroxyapatite-Based Magnetic Bionanocomposite as Pharmaceuticals Carriers in Chitosan Scaffolds - Casagrande-Denardin, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Hydroxyapatite (HA) is a bioceramic very similar to the mineral component of bones and teeth. It is well established that osteoblasts grow better onto HA-coated metals than on metals alone. Herein, the preparation of a new system consisting of magnetite (Fe3O4 ) and HA functionalized with oleic acid and simvastatin (SIMV), and incorporated in chitosan (CHI) scaffolds, was undertaken. HA was synthesized by the hydrothermal method, while Fe3O4 was synthesized by co-precipitation. The polymer matrix was obtained using a 2% CHI solution, and allowed to stir for 2 h. The final material was freeze-dried to produce scaffolds. The magnetic properties remained unchanged after the formation of the composite, as well as after the preparation of the scaffolds, maintaining the superparamagnetism. CHI scaffolds were analyzed by scanning electronic spectroscopy (SEM) and showed a high porosity, with very evident cavities, which provides the functionality of bone growth support during the remineralization process in possible regions affected by bone tissue losses. The synthesized composite showed an average particle size between 15 and 23 nm for particles (HA and Fe3O4 ). The scaffolds showed considerable porosity, which is important for the performance of various functions of the tissue structure. Moreover, the addition of simvastatin in the system can promote bone formation. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.